Constructing masculinity: A study on three community colorguard troupes in Kuala Lumpur / Syed Khairuzman Syed Zain - Syed Khairuzman , Syed Zain (2019)
This research focuses on the construction of masculinity within three community colorguard troupes in Kuala Lumpur. Colorguard has existed since the early days during the Civil War, where a military band would accompany soldiers on the battlefield. The color guard, or flag-bearer, would also march in battle with soldiers, carrying the “colors” that represents a particular nation. Flags and banners have been used by armies in battle to serve this purpose. As the years passed, colorguards became more correlated with marching bands. In a marching band, the colorguard is a non-musical section where the performers carry equipment such as flags and mock rifles made out of wood. The colorguard provides additional visual aspects to the overall performance, where the colors of the flags accompany and support the music in adding a layer of visual effect. In the United States, the modern colorguard activity is performed by males and females, incorporating dance such as ballet, jazz, modern, or interpretative dance while handling equipment such as flags, rifles, and sabers. In Malaysia, there are two types of colorguards, the female-dominated colorguards in high school marching bands, and community colorguard troupes consisting of majority males that performs without the accompaniment of a marching band. The practice of colorguards in high school marching bands, consisting of flag bearers with more elegant and feminized movements, is dominated by females. Community colorguard troupes, on the other hand, consist of predominantly male performers who use their advantage in physical strength to handle the equipment, such as rifles and sabers that were non-existent in high school marching bands. This ethnographic research examines three community colorguard troupes situated in Kuala Lumpur and how they construct masculinity within their performances. The first troupe is Guards Conspiracy, an all-male colorguard group. The second troupe is Vortex Winterguard, a mix-gendered group with majority males, and the third group is the Batteryheadz Colorguard Ensemble, an equally mix-gendered group. This research examines the construction of masculinity in colorguard that challenges the stigma of dancing being associated with femininity. This dissertation interrogates how masculinity is being constructed, performed, and asserted by men. This research offers a new perspective on masculinity within the field of dance in Malaysia.